The language of science and religion: An approach to understand the encounter between science and religion according to Ian G. Barbour - Fitria, Vita; Al Giffari, Haekal Adha (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2021)
The advancement of science is considered a reflection of age's development. At the same time, religion is placed as a relatively fixed essence. Their encounter creates undeniable continuous tensions. The problem generally lies in the question of how to apprehend unchanged issues within a dynamic context. This paper analyzed the encounter of science and religion with an observation of their language from the perspective of Ian G. Barbour. The library research method used in this paper to delve more in-depth the works of literature related to the topic discussed. Barbour responded with an argument that it is incorrect to keep polarization to choose between science and religion. The belief system of religion offers a broader frame of meaning in life. In comparison, science reveals a no more expansive range of human experience nor articulation of the possibility to transform human life as witnessed by religion. In observing their language as a tool for communication in religion and science, looking at their principles of verification and linguistic analysis, the contrast and comparison of their cognitive and non-cognitive function are emerged, including the evaluations and its limitations. Barbour states that basically, science and religion share synergic similarities. The dialogue to do to compare them is by sharing their similarities in method and concept prediction. One of those is by comparing their method, which shows their similarities and diversities. Science and religion share similar characteristics, namely coherence, comprehension and usefulness, and their methodology.Perkembangan sains bisa dianggap sebagai refleksi dari perkembangan zaman. Sementara Agama, ditempatkan sebagai essensi yang relatif tidak berubah. Pertemuan antara keduanya memungkinkan terjadinya ketegangan dengan perubahan yang terus menerus. Secara umum, persoalannya adalah bagaimana memahami hal-hal yang tak berubah itu dalam konteks yang selalu berubah. Ian Barbour menanggapi hal ini dengan argumen bahwa keliru melanggengkan dilema tentang keharusan memilih antara sains dan agama. Pertentangan yang terjadi di dunia Barat sejak abad lalu sesungguhnya disebabkan oleh paradigma yang keliru dalam memaknai hakikat sains dan agama. Kepercayaan agama menawarkan kerangka makna yang lebih luas dalam kehidupan. Sedangkan sains tidak dapat mengungkap rentang yang luas dari pengalaman manusia atau mengartikulasikan kemungkinan-kemungkinan bagi tranformasi hidup manusia sebagaimana yang dipersaksikan oleh agama. Barbour mengatakan  bahwa pada dasarnya antara sains dan agama terdapat kesamaan yang bisa disinergikan. Dialog yang dilakukan dalam membandingkan sains dan agama adalah menekankan kemiripan dalam prediksi metode dan konsep. Salah satu bentuk dialognya adalah dengan membandingkan metode sains dan agama yang dapat menunjukkan kesamaan dan perbedaan. Antara sains dan agama memiliki kesejajaran karakteristik yaitu koherensi, kekomprehensifan dan kemanfaatan. Begitu juga kesejajaran metodologis.